Developing H5P-Based Interactive Video Learning to Enhance Arabic Reading Comprehension in Madrasah Aliyah - Rinawati, Tiara Eki Wahyu; Ismail, Moh; Rochmat, Cecep Sobar (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
This study aimed to design, develop, and evaluate H5P-based interactive video media to improve Arabic reading skills (maha>rah al-qira>'ah) among tenth-grade students at Madrasah Aliyah Darul Ihsan Muhammadiyah Sragen. Employing the ADDIE model, the research followed systematic stages: analysis, design, development, implementation, and evaluation. Expert validation yielded high validity (average 4.7/5). The product was tested on 30 students using pre-test, post-test, questionnaires, and observations. Results showed a significant improvement in reading comprehension (t = 12.45, p < 0.001), with mean scores increasing from 58.3 to 82.5. Questionnaire data indicated enhanced motivation (average 4.6/5) and learner autonomy. The integration of text, audio, visuals, and interactive quizzes improved cognitive engagement, in line with Mayer’s Cognitive Theory of Multimedia Learning and Self-Determination Theory. The study proves that H5P-based media offer an effective, low-cost solution for developing Arabic reading skills and encourages further exploration of its long-term impact.